Leptin regulation of pubertal maturation in intact and pinealectomized female rats - Kacar, Emine; Dinc, Signem Eyuboglu; Yilmaz, Bayram; Kelestimur, Haluk (Tubitak Scientific & Technological Research Council Turkey, 2013)
Aim: To explore the roles of leptin and melatonin in early pubertal maturation. Materials and methods: Wistar female rats were used as experimental animals. Leptin was subcutaneously infused for 28 days through osmotic minipumps starting from postnatal day 15 (preweaning). Pinealectomy was performed on postnatal day 21 (weaning), and the animals were decapitated when estrus was detected by vaginal smearing. Results: Chronic preweaning, by peripheral infusion of leptin through subcutaneous routes, advanced the onset of puberty in leptin-treated sham and pinealectomized groups as determined by vaginal opening, while causing no significant change in serum estradiol levels and uterus weight. Mean body weights on the day of vaginal opening were significantly lower (P < 0.01) in leptin and pinealectomized-leptin groups compared to the control group. Conclusion: Preweaning leptin administration advances the onset of puberty regardless of body weight, and the pineal gland does not seem to have a modulatory effect on leptin-induced pubertal maturation.
Keywords: Leptin; pinealectomy; onset of puberty